The Asean Charter: An Analysis - Abdul Razak Ahmad (UUM Journal of Legal Studies, 2016)
The adoption of the ASEAN Charter in 2007 was believed to have transformed ASEAN to become a more institutional organisation with a profound framework and inclusive principles that act as a guideline to assist the process of disputes settlement and decision-making between the member countries. When the Eminent Persons Group (EPG) representing each of the countries addressed two main issues related to the recommendations to reform the norm and principles of ASEAN as well as the rights of the member countries to be put into the Charter, the ASEAN leader were not very receptive with the concept of using consensus decision-making process to impose sanctions and changes. Therefore, a watered-down ASEAN Charter was adopted portraying the un-readiness of the member countries to diverge away from the ‘ASEAN Way’ that had been implemented for the past 40 years. Despite the addition of two new principles that touches on the collective responsibility and enhancing consultation, the ASEAN Charter still does not exhibit the transformation of ASEAN as crafted by the EPG. The Charter also fails to provide pertinent mechanisms to address certain issues such as security and safety disputes. Hence, this article is written to confer the weaknesses of the ASEAN Charter and how important it is for ASEAN to move away for the usual norm of the ‘ASEAN Way’ in order to become a puissant organisation.